The Effect of Compensation and Motivation to Spirit at Work of Elementary School Teachers in Hulu Sungai Sub-District of Ketapang Regency - Igor Suryantoro; Maswardi M. Amin; M. Chiar (JETL (Journal of Education, Teaching and Learning), 2018)
This research is based on the results of early observation in elementary school in Hulu Sungai sub-district of Ketapang regency. Based on data obtained by the condition of elementary school teachers in Hulu Sungai sub-district indicated there is a decrease in teachers’ spirit at work. The Purpose of this research was to find: the effect of compensation and work motivation of elementary school teachers’ spirit at work in Hulu Sungai sub-district of Ketapang regency. This research uses a quantitative approach, where the pattern of relationship between variables to be studied using dual paradigm with two independent variables, that is to find the relationship of compensation (X1) with the spirit at work (Y), work motivation (X2) with spirit at work (Y), compensation (X1) and work motivation (X2) jointly on the spirit at work (Y). This research uses quantitative approach, where the pattern of relationship between variables and calculation using simple linear analytical technique and technique of doubled linear analysis. Result of the research based on 71 respondents showed that (1) There is significant effect of compensation to teachers’ spirit at work, 2) There is significant effect between work motivation to teacher’s spirit at work, (3) There is significant effect of compensation and work motivation against elementary school teachers’ spirit at work in Hulu Sungai sub-district of Ketapang regency.